Membrane fouling mitigation by fluidized granular activated carbon: effect of fiber looseness and impact on irreversible fouling - Wang, Jingwei (2022)
Membrane fouling mitigation by fluidized granular activated carbon (GAC) is well-acknowledged to be effective in mitigating external reversible fouling. However, the effect of fluidized GAC and fiber looseness on the alleviation of irreversible fouling is not known, which motivated the current study. Analyses included reversible and irreversible membrane fouling resistance, GAC particle velocities, foulant characteristics, permeate quality and membrane morphology. Results indicate that (i) membrane fouling resistances were significantly reduced by GAC fluidization and fiber looseness, with reversible and irreversible fouling respectively reduced by up to 17 and 35 times; (ii) advantages conferred by fiber looseness was tied to the decreased GAC particle velocities by about 10%, which implies a greater transfer of momentum from the fluidized GAC to the membranes; (iii) GAC scouring reduced 87% of reversible fouling and 48% of irreversible fouling, largely by microbial by-product-like substances but not so much by humic acid-like substances; whereas fiber looseness had a greater impact on the composition of the irreversible foulants; (iv) fluidized GAC particles and fiber looseness were more effective in alleviating the deposition of higher molecular weight organics in reversible fouling; (v) not only was the membrane integrity not compromised by the scouring GAC, but better permeate quality (i.e., 40% lower DOC in the permeate) was achieved; and (vi) roughness of the fouled membrane surface was 63% lower in the presence of GAC fluidization, which further reduced membrane fouling. This study thereby provides valuable insights towards the better design and operation of such fouling mitigation means for wastewater treatment.